2002
DOI: 10.2134/jeq2002.3310
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Retention and Release on Minerals and Soil in a Constructed Wetland

Abstract: Constructed wetlands are one method under investigation for the remediation of trace element-contaminated agricultural drainwater. A greater understanding of the retention of trace elements by the bulk soil and soil constituents is necessary for their safe and effective use. To determine the capacity of soil, calcite, and goethite-coated quartz sand for retention of As, Mo, and V under field conditions, an in situ method was used whereby permeable bags containing those minerals were placed near the sediment su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…Molybdenum is generally found in two oxidation states in nature, Mo(IV) and Mo(VI) (Fox and Doner 2002). It may exist as MoS 2 in reducing environments although the formation may be kinetically limited (Helz et al 1996).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Molybdenum is generally found in two oxidation states in nature, Mo(IV) and Mo(VI) (Fox and Doner 2002). It may exist as MoS 2 in reducing environments although the formation may be kinetically limited (Helz et al 1996).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…It may exist as MoS 2 in reducing environments although the formation may be kinetically limited (Helz et al 1996). Mo(VI) dominates under oxidizing conditions and is commonly present as MoO 2À 4 (Fox and Doner 2002). Therefore, the removal of MoO 2À 4 from wastewaters is of significant importance from an environmental point of view.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…On the other hand, arsenic may be retained by its adsorption onto clays and metal oxides, particularly those of Fe, Al and Mn (Smedley and Kinniburgh 2002). Generally, there is a good correlation between extractable iron and arsenic in soils and sediments around arsenic-enriched areas (Fox and Doner 2002). However, the adsorbed arsenic is released from clays and oxides by reductive desorption, or reductive dissolution, under reducing conditions (Smedley and Kinniburgh 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Specially, V displays inverted trend with Mn, Ce and Co. Fox and Doner (2002) reported that V was found in +3, +4, and +5 oxidation states in nature. Vanadyl is strongly adsorbed by solid phases, including organic and oxide-oxyhydroxide phases, whereas adsorption of the V anions is much lower than the cations (Wehrli and Stumm, 1989;Wanty and Goldhaber, 1992).…”
Section: Change Of Redox Conditions May Also Influence the Distributimentioning
confidence: 98%
“…Previous studies on the chemical speciation of redox-sensitive elements were performed for seasonally saturated soils (Flessa and Fischer, 1992;Fox and Doner, 2002;Weber et al, 2009), bioturbated sediments (Aller, 1994;Collins and Kinsela, 2010), and forest soils (Clark et al, 1998;Silver et al, 1999). Comparatively, less information is available concerning redox transformation of trace metals during weathering of granitic rocks (Middelburg et al, 1988;van der Weijden and van der Weijden, 1995).…”
Section: Introductionmentioning
confidence: 99%